2018
DOI: 10.1021/acs.cgd.8b01557
|View full text |Cite
|
Sign up to set email alerts
|

Pendant Affected Crystallization Behaviors of Cyclic Poly(ε-caprolactone)

Abstract: The topology of macromolecules is an important concept of polymer science, and cyclic polymers are the simplest model for studying the effects of topology. To explore the topological effects on crystallization behaviors of cyclic poly­(ε-caprolactone) (PCL), the cyclic and linear PCLs with anthracene groups in the main chain were used to investigate the crystallization behavior as PCL necklace with pendant and PCL asalato. Polarizing optical microscopy showed spherulite growth, and in situ wide-angle X-ray sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Ring closing is a popular method for small-scale synthesis of cyclic polymers. This method involves cyclizing a linear polymer by linking α- and ω-chain-ends to afford a cyclic topology. ,, Ring closing enables the synthesis of a wide variety of cyclic polymers containing diverse repeat units, is tolerant to different functional groups, and can provide precise control over molecular weights and dispersity . However, in addition to intramolecular ring-closing, intermolecular chain elongation inevitably occurs, leading to linear polymer impurities, though recent work indicates the linear impurities can be minimized, and their influence on solution phase properties is minimal .…”
mentioning
confidence: 99%
“…Ring closing is a popular method for small-scale synthesis of cyclic polymers. This method involves cyclizing a linear polymer by linking α- and ω-chain-ends to afford a cyclic topology. ,, Ring closing enables the synthesis of a wide variety of cyclic polymers containing diverse repeat units, is tolerant to different functional groups, and can provide precise control over molecular weights and dispersity . However, in addition to intramolecular ring-closing, intermolecular chain elongation inevitably occurs, leading to linear polymer impurities, though recent work indicates the linear impurities can be minimized, and their influence on solution phase properties is minimal .…”
mentioning
confidence: 99%
“…According to the literatures, the crystallization behavior of linear polymer and cyclic polymer differs due to the distinct topological structures. To investigate the impact of stepwise modification on the crystallization and melting behavior of PCL polymers, differential scanning calorimetry (DSC) was performed. As shown in Figure S9, the crystallization temperature changed greatly after stepwise modification for the (PCL 10 –OH) 2 system, while the crystallization temperature remained similar for the (PCL 40 –OH) 2 analogue.…”
Section: Resultsmentioning
confidence: 99%
“…39 Entangled c-PCLs containing bi-anthracene groups showed slower crystallization kinetics than their linear counterparts. 40 These results can be understood through the restriction of obstacles on chain dynamics. 41,42 Further work showed that the inhibitory effect of end groups on the crystallization kinetics of linear PCLs weakened with increasing molecular weight, and the critical molecular weight (M c ) of the two ends modified PCLs is about 8 kg mol À1 .…”
Section: Introductionmentioning
confidence: 99%